Financial Market Globalization, Symmetry-Breaking, and Endogenous Inequality of Nations - Matsuyama, Kiminori (Econometrica, 2004)
This paper investigates the effects of financial market globalization on the inequality of nations. The world economy consists of inherently identical countries, which differ only in their levels of capital stock. Each country is represented by the standard overlapping generations model, modified only to incorporate credit market imperfection. An integration of financial markets affects the set of stable steady states, as it changes the balance between the equalizing force of the diminishing returns technology and the unequalizing force of the wealth-dependent borrowing constraint. The model is tractable enough to allow for a complete characterization of the stable steady states. In the absence of the international financial market, the world economy has a unique steady state, which is symmetric and stable. In the presence of the international financial market, symmetry-breaking occurs under some conditions. That is, the symmetric steady state loses its stability and stable asymmetric steady states come to exist. In the stable asymmetric steady states, the world economy is endogenously divided into the rich and poor countries; the borrowing constraints are binding in the poor but not in the rich; the world output is smaller, the rich are richer and the poor are poorer in any of the stable asymmetric steady states than in the (unstable) symmetric steady state.